UTILIZING DIGITAL MARKETING IN SELLING TOUR PACKAGES: A SYSTEMATIC REVIEW OF LITERATURE - Dhia Fadhila Hendra (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2025)
The advancement of digital technology has transformed how consumers search for information and purchase tourism products. Digital marketing has become a vital strategy for tourism businesses to expand their market reach and effectively engage with consumers. This study aims to analyze the utilization of digital marketing in selling tour packages in the modern era. By employing a qualitative descriptive approach through an integrative literature review, this research examines various secondary sources, including journal articles, books, and official reports related to digital marketing and tourism. The author employed thematic analysis to identify trends and effective strategies in digital marketing. The findings reveal that social media platforms such as Instagram and TikTok effectively attract young tourists through engaging and interactive visual content. Additionally, electronic word of mouth (e-WOM) has a significant influence on consumers’ purchasing decisions regarding tour packages. This study recommends that tourism businesses optimize their use of social media and incorporate interactive content to enhance customer loyalty and sales. Consequently, digital marketing serves as an effective tool to compete in the tourism industry.